(untitled) - Van Vuuren, Jurie Jansen

Willingness of entrepreneurs to use Broad-Based Black Economic Empowerment to build cross-race business alliances (University of Pretoria, 2025)
Thesis (PhD Business Management (Entrepreneurship))--University of Pretoria, 2024.